IDENTITY CONSTRUCTION AND CLASSROOM PARTICIPATION OF AN EFL STUDENT WITH A HEARING IMPAIRMENT IN AN ISLAMIC-BASED SCHOOL - Nurmala Nurmala; Durratul Hikmah; Eky Arisandy (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
While studies on identity construction and classroom participation among English as a Foreign Language (EFL) learners are abundant, limited attention has been given to how students with hearing impairments experience these processes within religious educational contexts. Addressing this gap, the study explored how an Indonesian female EFL student with a hearing impairment constructed her identity and participated in classroom learning in an Islamic-based school. Drawing on data from in-depth semi-structed interviews, the study employed Braun and Clarks (2006) thematic analysis to interpret the participants lived experiences. The finding reveal that the participants identity developed through a series of stages: the orientation, the adjustment, the difficulty, the settlement, and identity development. Her identity construction was shaped by emotional resilience, religious values, and strong support from family, peers, and teachers. In parallel, her classroom participation evolved from passive observation to active involvement through adaptive strategies, such as preparing questions and engaging in peer interaction. This study illustrated how identity construction and classroom participation are intertwined, particularly for students with disabilities navigating inclusive learning environments. It also underscored the importance of culturally and religiously responsive support systems in fostering self-growth and academic among marginalized learners.